THE INFLUENCE OF WORKING POSITIONS, WORKING PERIOD, AND DURATION OF WORK IN LOW BACK PAIN INSIDENCE AMONG PACKING WORKERS PT PHAPROS Tbk - M. Riza Setiawan; Merry Tiyas Anggraini; Millati Rahmatika (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Low Back Pain (LBP) is a phenomenon that is often complained of the elderly, but it was likely experienced by the young. This phenomenon is common in every job, especially the industrial workers are still using manpower in terms of handling the material. The transfer of material manually is not done ergonomically will cause accidents. Position work is continuous static and can cause health problems such as LBP is capable of interfering with work productivity. The purposes of this study is to identify theinfluence between working positions, working period, and  duration of work in low back pain incidence on packing workers PT PHAPROS Tbk. Semarang in 2016. This study was an observational study with cross sectional analytic analyzed with Chi square correlation test and Spearman correlation which includes univariate and bivariate analysis. The number of  samples with random sampling techniqueswere 100 packing workers PT. Phapros Tbk Semarang in August-October, 2016. Most of workers complained of moderate pain (42%). The results of the bivariate analysis showed that the position of the work-related complaints LBP (p = 0.000). There was a significant correlation between working period with complaints of LBP (p = 0.000), and there was a significant correlation between the duration of workwith complaints of LBP (p = 0.000). The results indicate that the significant correlation between the working position, working period, and duration of work with the complaint LBP. Working position is the most influence variable on the incidence of LBP. The importance of maintaining the position of the work, as well as effectively manage their work time so as to minimize the occurrence of LBP pain.  Keywords: working position, working period, duration of work, Low Back Pain